ROLE OF MARKETING STRATEGIES IN INNOVATIVE DEVELOPMENT OF RAILWAY TRANSPORT SYSTEM AND IMPROVEMENT OF MANAGEMENT MECHANISMS (Marketing Journal, 2025)
This article evaluates the integration of marketing strategies into the management mechanisms of the railway transport system based on empirical and comparative analysis. Drawing from the cases of Europe, India, and Indonesia, it explores how marketing adapts to user needs, diversifies services, and improves system efficiency through digital solutions. Findings show that marketing plays a strategic role at the system -wide level of transport governance.
Keywords: railway transport; innovation management; marketing strategy; user experience; digital services; system efficiency